Teachers and learners perspectives on learning mathematics for at-risks students - Abu Bakar, Kamariah; Ahmad Tarmizi, Rohani; Md Nor, Sharifah; Wan Ali, Wan Zah; Hamzah, Ramlah; Abdul Samad, Arshad; Jamian, Abdul Rashid (Elsevier, 2010)
The purpose of the study is to identify problems related to mathematics and science learning faced by students as perceived by the Form two At-Risk students, and as perceived by the mathematics and science teachers when teaching the subjects, to examine students’ mathematics and science learning climate, to identify teaching strategies frequently used by the mathematics and science teachers, and to identify effective teaching strategies perceived not feasible to be used by the teachers for At-Risk students. This research employed a quantitative research method with a descriptive survey design. The survey was conducted using three sets of Likert-type questionnaires for mathematics and science teachers, and the secondary school students. A total of 30 mathematics and 31 science teachers, and 1575 Form Two students were the respondents of this study. Findings showed that there was a need for a specific curriculum for at-risk students in Malaysia focusing on basic knowledge and skills and simplifying the content of the mathematics and science syllabuses tailored towards At-Risk students.